Bladder Cancer Sample Handling and Reporting: Pathologist's Point of View - Mazzucchelli, Roberta; Marzioni, Daniela; Tossetta, Giovanni; Pepi, Laura; Montironi, Rodolfo (Frontiers in Surgery, 2021)
The best management for patients with bladder cancer is closely related to collaboration between urologists and pathologists. Urologists should provide adequate clinical information to pathologists and these should use standard and unambiguous terms, understandable to clinicians for grading and staging bladder cancer. This review focused on the main problematic aspects of clinical relevance concerning the bladder carcinoma and provided a comprehensive view of recommended elements for handling and reporting bladder tumor specimens on the base of more recent literature.